Punishment in English Language Classroom: Forms and Effects - Poudel, Guru Prasad (English Language Teaching Perspectives, 2022)
Students should be cared for with tender love and kindness in the basic level classes. However, we experience the use of punishment. A teacher’s punishment can create multiple effects on the students’ learning. Considering this, the present article aims to find out the forms of punishment and their effects on students’ learning of English. It has been developed out of the research work on the issue of punishment in English language teaching. The study followed a phenomenological research design using the qualitative interpretative method. The data were elicited by using participant observation, focus group discussion and exit interviews. A basic level school in the Gorkha district was selected and the ten different classes of English teachers were observed. A Focus group discussion was held with the students and finally, an exit interview was taken with the teacher. The findings of the study depict that teachers exercised punishment on the students in the forms of scolding, slapping, disguising, threatening, and advising. The students’ experienced that their teacher was not friendly to them as he exercised punishment to control their behaviours. However, the teacher shared his compulsion to use punishment due to the students’ insincerity. Both the students and the teachers realized the formative and destructive role of the punishment tools according to the situation. The results enabled us to conclude that although teachers and educators prefer learner-centred pedagogy in basic level classes, still they are using punishment as a strategy to take control over the class and to discourage the students’ misbehaviours.